Application of Problem-Based Learning (PBL) Model to Improve Literacy Skills of Grade XA Students at SMANOR Tadulako Palu - Alfadillah, Dian Husnaya; Non Shamdas, Gamar Binti; Jihad, Jihad (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
IThis study aims to test the effectiveness of the Problem-Based Learning (PBL) model in improving the literacy skills and reading interest of students in class XA at SMANOR Tadulako Palu. This study used a classroom action research design conducted in two cycles involving 22 students. Data were collected through literacy tests and reading interest questionnaires, then analyzed descriptively and through ANOVA and Tukey's HSD tests. The results of the study show a significant increase in literacy skills, with the average score increasing from 38.18 in the pre-cycle to 65.91 in Cycle I and 90.91 in Cycle II (p < 0.05). In terms of reading interest, the median score increased from 44 in Cycle I to 65 in Cycle II, with a wider score range and a more even distribution. ANOVA analysis confirmed that the increase was statistically significant (p < 0.05). These findings indicate that the implementation of PBL is not only effective in strengthening students' literacy skills, but also in fostering a more equitable interest in reading across different achievement groups. Thus, PBL is recommended as an alternative learning strategy to improve literacy and motivate reading in secondary schools.